Income and price elasticities of food demand (E-FooD) dataset: Documentation of estimation methodology - Ecker, Olivier; Comstock, Andrew R. (International Food Policy Research Institute, 2021)
This document presents the estimation methodology for the Income and Price Elasticities of Food Demand (E-FooD) Dataset, Version 1.0. The E-FooD Dataset focuses on developing countries. It will be periodically updated to add data for more countries and from new survey rounds. The dataset is publicly available and can be downloaded from: https://doi.org/10.7910/DVN/OXZ0H6. Income and price elasticities of food demand are economic measurements of the responsiveness of food consumption to income and price changes for a group of consumers. The income elasticity of food demand measures the percent change in the consumption of total food or a certain food item or group of food items to a percent change in the real income of consumers. The price elasticity of food demand is a measurement of the percent change in the consumption of a certain food item or group of food items (or total food) to a percent change in the price of this food item or group of food items (or total food)—or the price of another food item or group of food items. The own-price elasticity measures the consumption response to the price change for the same food item or group of food items. The cross-price elasticity measures the change in the consumption of a food item or group of food items to the price change of another food item or group of food items. Income and price elasticities of food demand can be econometrically estimated from observational data. Income and price elasticities of food demand elasticities have a variety of uses. First, the elasticities have a direct interpretational value of consumer behavior, as they reflect latent consumer preferences for different foods. They are means to understand how consumers are expected to adjust their food consumption in response to a marginal increase or decrease of their real income or of the prices of the foods they consume. This provides critical, policy-relevant information for assessing the likely consumption effects of economic growth and (relative) price changes due to economic shocks from global food price crises, extreme weather events, armed conflicts, and pandemics, for example. Second, elasticities of food demand are input parameters in various models and analyses, ranging from models for business decision making to market and international trade models and economy-wide models such as computable general equilibrium (CGE) models. Third, elasticities of food demand can be directly used for simulations on, for example, the likely impacts of economic policies and shocks on consumer diets and food security, as well as projections of food consumption trends. The E-FooD Dataset provides a valuable data source for researchers, analysts, and policymakers to address a variety of food demand issues in several developing countries, and it is publicly available free of charge. Users are requested to properly cite the dataset and the estimation methodology in their publications or other products that make use of it.